Talaromikosis Marneffei - Sem S. Surja; Robiatul Adawiyah; Retno Wahyuningsih (Jurnal Ilmu Kedokteran, 2018)
Talaromycosis marneffei is a mycotic disease caused by Talaromyces marneffei which primarily infect immunocompromised patient. This disease is endemic in Southeast Asia, and Indonesia consider as endemic area due to a case of tourist who got the infection after visiting Indonesia. Diagnosis was made based on clinical suspicion with laboratory confirmation. Clinical manifestations are not specific, such as fever, anemia, weight loss, lymphadenopathy, hepatomegaly, splenomegaly, respiratory disorder, and cutaneous manifestation. Histopathology and culture are the most common examination performed for diagnosis. In histopathology examination, fungi appear as fission arthroconidia cells which shape round to oval, with cross wall formation inside or outside macrophage and histiocyte. Thermal dimorphism characteristic can be observed in fungal culture. Fungi grows as mold at 25oC-30oC and as yeast at 37oC. Definitive identification of T. marneffei was done by molecular examination using primers derived from ITS region as primary marker and beta tubulin region as secondary marker. Talaromyces marneffei is sapronosis, that transmitted via inhalation of conidia from environment.